Near-field coseismic deformation across the Sürgü-Erkenek segments revealed by integrated GNSS and InSAR analysis following the 2023 Kahramanmaraş Earthquakes, Türkiye - Tiryakioglu, Ibrahim; Solak, Halil Ibrahim; Gezgin, Cemil; Aladogan, Kayhan; Poyraz, Fatih; Aksoy, Ercan (Indian Acad Sciences, 2026)
The two successive large earthquakes (Mw 7.7 and Mw 7.6) that struck along the East Anatolian Fault Zone (EAFZ) on 6 February 2023, broke a long-lasting seismic quiescence in the region and produced a surface rupture exceeding 500 kilometres. These earthquakes triggered a devastating series of events that resulted in extensive structural damage and significant loss of life, underscoring the critical importance of reassessing the region's seismogenic potential and the associated changes in environmental stress. This study focuses on the coseismic and near-field deformation of the Erkenek (ES) and S & uuml;rg & uuml; segments (SS), where a dense GNSS network - supplemented by SAR-based pixel offset tracking - captures deformation patterns using previously unpublished GNSS stations situated between the two main shocks. The results of this study reveal heterogeneous displacement patterns and opposing directional motions between ES and SS, indicating torsional deformation along the S & uuml;rg & uuml; Segment - a fault that remained unruptured by the doublet but exhibits elevated Coulomb stress. This torsional mechanism is significant as it highlights the development of localised strain concentration zones that may influence future rupture propagation paths. Such strain localisation may modify stress transfer patterns between adjacent fault segments and therefore has important implications for segment interaction and seismic hazard assessment. The epicentres and focal mechanism solutions of these destructive strike-slip earthquakes, together with the observed displacement patterns, indicate the presence of a localised shear zone between the Erkenek and S & uuml;rg & uuml; segments, where differential left-lateral motion of adjacent fault blocks produced large and spatially variable displacements along the S & uuml;rg & uuml; segment. These findings, when integrated with kernel density-based aftershock distributions, Coulomb stress transfer analyses, and b-value variations consistently indicate elevated post-seismic stress along the unruptured S & uuml;rg & uuml; Segment. These observations collectively demonstrate that the SS remains a critical locus of strain accumulation and should be considered a priority in future seismic hazard assessments.
Keywords: Coseismic Deformation; Kahramanmara & Scedil; Earthquakes; East Anatolian Fault Zone; S & Uuml;Rg & Uuml; Segment; Gnss; Torsional Deformation; Sar Pixel Offset Tracking